Characterizing substance use in a sample of lesbian, gay, bisexual, and transgender adults in Mexico. Issue 1 (1st December 2020) - Hoetger, Cosima; Rabinovitch, Annie E.; Henry, Richard S.; Aguayo Arelis, Adriana; Rabago Barajas, Brenda Viridiana; Perrin, Paul B.
Abstract: Background : Research from high-income countries on substance use among lesbian, gay, bisexual, and transgender (LGBT) adults is growing; however, limited empirical research exists on LGBT adults in Mexico. Filling this gap is critical as LGBT adults experience unique stressors that may place them at risk for substance use-related health outcomes. Objectives : This study sought to characterize substance use prevalence and magnitude among a convenience sample of Mexican LGBT adults. Methods : A cross-sectional online survey was conducted using a sample of Spanish-speaking, self-identified LGBT adults ( n  = 92) residing in Mexico who were recruited through online forums of LGBT-focused organizations. Descriptive and frequency analyses were conducted. Results: Participants predominantly identified as cisgender men ( n  = 44) and gay/lesbian (n = 68). Participants reported high rates of past 90-day legal substance use (>93% for alcohol and >57% for tobacco). The most commonly reported illicit drug used in the past 90 days was marijuana (>29%). Conclusions : While the sample reported lower prevalence and magnitude of substance use relative to other Mexican or United States LGBT samples, the findings highlight that legal and illicit substance use presents health risks for Mexican LGBT individuals. LGBT identity-affirming substance use treatment may reduce substance use-related health burden among this population.